Can Radiological Imaging Accurately Predict the Length of the Ureteral Defect/Stricture Following Ureteral Injury? - Basiri, Abbas; Ghaed, Mohammad Ali; Amini, Erfan; Dadpour, Mehdi (Urology Journal, 2025)
Purpose: The incidence of ureteral injury is increasing due to extensive application of the endourological procedures. In the present study, we evaluated the accuracy of imaging studies in predicting length of defect in patients with ureteral injury. Methods: We reviewed data of all consecutive patients who underwent endourological management for ureteral injury in our institution from Jan 2020 to Jan 2023, to assess the accuracy of radiological evaluations in determining the length of ureteral defect. We compared the radiological imaging results with intraoperative findings to determine its diagnostic accuracy. Results: We report data on accuracy of preoperative imaging and outcomes of endourological management in 5 patients who presented with apparently long ureteral defects in preoperative radiological evaluations following ureteral injury. The mean age was 42[30.5-42.5]. three of five were male. The mean time from injury to ureteroscopic management was 12.5±7.5 days. The mean follow up time was 7.3±2.2 months. Our experience showed that radiological evaluations have the potential to overestimate the length of defect. Conclusion: Radiological evaluations following ureteral injury have the potential to overestimate the length of defect and therefore endoscopic evaluations and intraoperative imaging studies are necessary to accurately determine the length of defect and appropriate management. However, endourological management is safe and efficient in treating patients with short segment ureteral defect/injury.